Prospective observational study for appropriateness of blood and blood components therapy in children up to 16 years of age admitted in a tertiary care hospital - Hegade, Vinayaka P.; Rao, Anjana H. (International Journal of Contemporary Pediatrics, 2018)
Background: Blood component therapy is a rational replacement therapy of proven clinical value and efficacy, but it is a double-edged sword as it is associated with many hazards of transfusion reaction. Because of ease of availability and gap in the knowledge of medical professional’s blood products are being used very liberally leading to huge mismatch in the demand and supply of life saving blood product. Methods: Prospective cross-sectional observational study was done over a period of 1 year in a tertiary hospital, in western part of India. 225 events of blood component therapy were studied in neonates (<1month) and pediatric (1month-16years) age groups. Indications and reactions to blood components therapy were studied in both the groups. Each component therapy was considered as one event and its indication was compared with standard guidelines for terming it as appropriate or inappropriate. Results: Out of total 225 events of transfusions, most commonly used was PRBC (48.9%) followed by FFP (24.9%), platelet (16.0%), IVIG (9.8%) and whole blood (0.4%). Authors found that overall 17.3% of the component therapy were inappropriate( neonates 10.2% and 7.1% in the rest). Most commonly misused blood product was FFP (37.5%) followed by IVIG (22.7%), platelets (16.7%) and PRBC (6.4%). Conclusions: Regular audit of blood and its component usage is essential to assess the blood utilization pattern and set ideal policies in all the medical specialties to make it appropriate, ensure availability and save patients from its hazards.